Visionary stories about teaching and learning in a Swedish Art and Music School : A practice-based inquiry - Wikström, Hannes ; 0009-0008-7458-8229 (Nordic Network of Research in Music Education 2025, Hurdal, Norway, 2025-03-08 - 2025-03-10, 2025)
The Swedish music and arts school (SAMS) has been described as “a foundation for Swedish culture, where children and youth are given opportunities to express themselves through dance, fine art, drama, music or other art forms” (Öhrman & Holmdahl, 2022, s. 103). Current debates have questioned SAMS capacity to meet contemporary needs, revolving around themes such as broadening of target groups, diversification of learning strategies and introduction of new SAMS subjects. The following presentation offers a brief outline of a PhD project (compilation thesis) within the field of music education, very much in its early stages. The study positions itself within the category of practice based educational research in that it seeks to develop educational pedagogic practice, in close collaboration with SAMS and its actors. Based on similar projects, the research design makes use of a combined researcher insider position in what could be described as an explorative case study, focusing on a specific SAMS’s educational activities and its development. Collecting of data and analytical work will be carried out as an ongoing iterative process, using a methodological triangulation drawing on open interviews, dialogical focus group activities and workshops. The creative and aesthetic nature of SAMS subjects are also intended to be reflected throughout the project’s phases and in its output. Implications could include e.g. creation of tools for pedagogical development in practice, such as a guide for collaborative interdisciplinary SAMS projects’, but also spreading of the research model and method(s) to other similar pedagogical milieus. Challenges and ethical consideration of vital importance has been identified in terms of 1) how informed consent and committed participation from all subject-groups can be achieved; 2) ethical challenges surrounding positionality in practice-based research; 3) maintaining a balance between meeting the needs of the academic field, versus the practice’s.
Keywords: Musikundervisning; Kulturskola